Water in the Roman world : engineering, trade, religion and daily life - Henig, Martin,; Lundock, Jason, (Archaeopress Roman archaeology ;, 2022)
Offering a wide and expansive new treatment of the role water played in the lives of people across the Roman world, papers consider ports and their lighthouses; water engineering, whether for canals in the north-west provinces, or for the digging of wells for drinking water; baths for swimming; and spas.